Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1097/00007890-199202010-00045
|View full text |Cite
|
Sign up to set email alerts
|

Inbibition of Liver, Kidney, and Intestine Regeneration by Rapamycin

Abstract: For a decade, liver transplant recipients have been treated with cyclosporine, a drug with modest hepatotoxicity (1). Concern that CsA might inhibit hepatic regeneration or the ability of the transplanted liver to adjust its size to that of the recipient prompted studies by Makowka et al.(2) and others (3-5), which showed that regeneration actually was enhanced. A newer unrelated immunosuppressive agent, FK506, has the same properties (5). In addition, these 2 drugs have other actions that are collectively cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…In the present study, we found that EVR delayed liver regeneration. This result is consistent with that reported for sirolimus 27,28 . Toso et al reported that introduction of sirolimus immediately after LDLT inhibited hepatocyte proliferation 29 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, we found that EVR delayed liver regeneration. This result is consistent with that reported for sirolimus 27,28 . Toso et al reported that introduction of sirolimus immediately after LDLT inhibited hepatocyte proliferation 29 .…”
Section: Discussionsupporting
confidence: 91%
“…This result is consistent with that reported for sirolimus. 27,28 Toso et al reported that introduction of sirolimus immediately after LDLT inhibited hepatocyte proliferation. 29 Ideally, liver regeneration should be evaluated in the absence of liver damage (e.g., infection or rejection) because liver weight and Ki-67 can be affected by liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…Rapamycin is the canonical inhibitor of mTORC1 and has been used extensively for studying mTORC1 function in various tissues. In the intestine, systemic administration of rapamycin has been shown to reduce intestinal surface area in rabbits, 9 disrupt intestine regeneration in rats, 10 cause diarrhea in human beings, 11 and inhibit intestinal regeneration in acute inflammatory bowel disease. 12 Repression of mTORC1 in Paneth cells provides a niche for enhancing intestinal stem cell proliferation while keeping rates of proliferation low in transient amplifying cells.…”
mentioning
confidence: 99%
“…The mTOR pathway, particularly mTORC1, helps to maintain the structure of the mammalian intestinal mucosa 8 and is important in stem cell self-renewal 9 . Inhibition of mTOR by rapamycin has been shown to disrupt intestinal growth and regeneration in healthy animals 4, 10 .…”
Section: Introductionmentioning
confidence: 99%